The presence of place In the stories of the stream of consciousness - Maya, Fakher; Jaber, Youssef; Alhafi , Houda (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The presence of place had a distinctive position in the stream of consciousness that made it able to show and rise the humanbeing's problems precisely and frankly from many different views. Probably. The most important problem is making the emotional relationship eminent and this what relates the human being to the place and the effect of that on turning the relation of the human being with the place into a mutual one that made the perception of the place nourish the emotion and vice versa and within this concept, that mutual relationship has uncovered the depth of the gap between two worlds which neither of them belongs to the other and they are the inner world and the outer one clearing the self-crisis in its searching for domestic place or in its wish to escape from frightful place to a safer one and because the awareness has no limits in the pre-speaking levels, the confused human thoughts and intelligence have accompanied his constant searching for the place and his dream in achieving his belonging goal.